Number of human-brown bear ( Ursus arctos ) and human-Persian leopard ( Panthera pardus ) incidents by age class (a), gender (b), group size (c) of people, Iran, 2012–2020. - Jamshid Parchizadeh (11172294); Jerrold L. Belant (7852490) (2021)
Number of human-brown bear ( Ursus arctos ) and human-Persian leopard ( Panthera pardus ) incidents by age class (a), gender (b), group size (c) of people, Iran, 2012–2020.